2013
DOI: 10.1111/codi.12381
|View full text |Cite
|
Sign up to set email alerts
|

Completion surgery following transanal endoscopic microsurgery: assessment of quality and short‐ and long‐term outcome

Abstract: Patients having full-thickness TEM excision, distally placed lesions and a long interval (> 7 weeks) to CS were likely to have an inferior TME specimen. The results confirm that CS after TEM does not negatively influence local recurrence and survival, but the reduced disease-free survival in patients with an inferior specimen is of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
60
2
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 18 publications
(29 reference statements)
9
60
2
5
Order By: Relevance
“…TME following TEM is associated with a higher complication rate, than TME alone, especially shown in the high rate of anastomotic leaks within 30 days. Even though the literature on completion TME is scarce, the 18% anastomotic leakage after completion TME found in our study doubles the rate found in the study from Hompes et al [21]. They did report that in half of the cases, the dissection was considered difficult due to the disruption of the normal tissue planes at the TEM site.…”
Section: Discussionsupporting
confidence: 47%
“…TME following TEM is associated with a higher complication rate, than TME alone, especially shown in the high rate of anastomotic leaks within 30 days. Even though the literature on completion TME is scarce, the 18% anastomotic leakage after completion TME found in our study doubles the rate found in the study from Hompes et al [21]. They did report that in half of the cases, the dissection was considered difficult due to the disruption of the normal tissue planes at the TEM site.…”
Section: Discussionsupporting
confidence: 47%
“…However, the increased morbidity (53%) and risk of local recurrence (HR 6.8; 95% CI 2.7-17.0; p < 0.0001) associated with completion radical surgery compared to immediate TME is of concern [1][2][3]. Completion TME is also associated with increased perforation of the rectal wall (up to 20% of patients), prolonged operating time, and increased rate of permanent stoma rate compared with primary TME [1][2][3][4]. Difficulty of completion surgery is mainly suggested due to fibrosis or inflammation of the perirectal tissue at the previous TAMIS-site in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…With the implementation of population screening programs for colorectal cancer and longer life expectancy, the incidence of elderly patients being diagnosed with early rectal cancer increases. Rectal preserving therapy is appealing for these patients as radical rectal surgery has been correlated with higher colostomy rate, higher morbidity, and poorer functional outcomes [1][2][3][4][5][6][7][8]. Commonly used platforms for full-thickness local excision include transanal endoscopic microsurgery (TEM), transanal endoscopic operations (TEO) and the GelPoint® Path port which offer a safe and curative therapy when performed for large rectal adenomas and low-risk T1 carcinoma, including tumors smaller than 3 centimeters in size,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Autre piste, c'est peut-être de limiter l'insufflation dans cette indication et ce d'autant que Hompes et al ont rapporté que la TEM était un facteur de risque indépendant de récidive après proctectomie de rattrapage [1]. Finalement, troisième possibilité, c'est de réaliser un traitement systé-matique par radio chimiothérapie en préopératoire en cas de proctectomie de rattrapage, et ce d'autant que Gagliardi et al rapportaient un taux de 35 à 40 % de tumeur résiduelle sur les pièces de proctectomie et ce malgré une exérèse locale initialement complète [2].…”
Section: Docteur Anyla : On N'a Pas Attendu Deux Ans On Vous Donne Lunclassified